Pemberdayaan Masyarakat Melalui Pemanfaatan Jamu Sebagai Minuman Herbal Pada Masyarakat Desa Badrain Kabupaten Lombok Barat - Sri Anjarwani; Ernawati; Maulida Atrianingsih; Firman Ali Rahman (Yayasan Tajuk Indonesia, 2025)
The purpose of this community service activity is to provide information and socialization about the use of betel leaf and tamarind herbal medicine as herbal drinks to the community in Badrain Village, Narmada District, West Lombok. The community service method used is the community service method. The results of this community service activity confirm that the use of herbal plants such as betel leaf, tamarind, turmeric, and ginger as the main ingredients of traditional herbal medicine provide extensive health benefits and are empirically proven. This activity not only helps increase public awareness of the benefits of herbal medicine, but also fosters their skills in producing healthy and safe concoctions. This service also has a positive economic impact. Utilizing plants that are easily accessible and relatively inexpensive, the community is encouraged to produce their own herbal medicine, which in turn can be a source of additional income. Through this approach, the community service program has contributed to empowering the community economically and socially. In addition, this program also preserves the tradition of using herbal plants that have been known for generations. Knowledge of proper processing techniques, such as drying, mixing, and storage, is an important part of what is taught to the community. Overall, this service has had a positive impact by improving the quality of public health, opening up new economic opportunities, and encouraging the preservation of local culture.